Detecção de anticorpos anti-Toxoplasma gondii em animais de uma comunidade rural do Mato Grosso do Sul, Brasil - Marques, Joil Moreira; Isbrecht, Fabiane Beatriz; Lucas, Thays Mizuki; Polido Guerra, Isabela Maria; Dalmolin, Aline; da Silva, Rodrigo Costa [UNESP]; Langoni, Hélio [UNESP]; da Silva, Aristeu Vielra (Universidade Estadual de Londrina (UEL), 2009)
The rate of anti-Toxoplasma gondii antibodies was evaluated in equines, cats, dogs, poultry, pigs, cattle and sheep of farms in Eldorado, southern Mato Grosso do Sul. Blood samples were collected and sera were examined by the modified agglutination test (MAT), considering positives samples reactants with titers >= 25. Rates of reactor animals in the antibody detection test were: 22.89% (46/201) in poultry, 5.15% (20/388) in cattle, 47.61% (20/42) in dogs, 60.87% (14/23) in equines, 57.14% (8/14) in cats, 14.7% (5/34) in pigs. None of the sheep (0/14) were positive. High antibody rates were found in several species, a fact that raise concerns due to the possibility of risk to humans, once these animal species either share the same source of infection with humans or are food sources for them.
Anti-Toxoplasma gondii antibody detection in animals from farms of a rural community of south of Mato Grosso do Sul, Brasil
Keywords: Toxoplasma gondii; antibodies; epidemiology; rural